ADDING AGENT CONCEPTS TO OBJECT EVENT MODELING AND SIMULATION - Wagner, Gerd; Nardin, Luis G. (2018 Winter Simulation Conference (WSC), 2018)
Object Event Modeling and Simulation (OEM&S) is a general Discrete Event Simulation paradigm combining object-oriented modeling with the event scheduling paradigm. We show how to extend OEM&S by adding concepts of agent-based modeling and simulation, resulting in a framework that we call Agent/Object Event Modeling and Simulation (A/OEM&S). The main point for such an extension is to define agents as special objects, which are subject to general (physical) laws of causality captured in the form of event rules, and which have their own behavior allowing them to interact with their inanimate environment and with each other. Because agent behavior is decoupled from physical causality, an A/OE simulator consists of an environment simulator, which simulates the physical world (the objective states of material objects), and agent simulators, which simulate the internal (subjective) states of agents and their behaviors.